Lyapunov-type inequalities for quasilinear systems with antiperiodic boundary conditions - Youyu Wang; Yannan Li; Yongzhen Bai (Український математичний журнал, 2013)
We establish some new Lyapunov-type inequalities for one-dimensional p-Laplacian systems with antiperiodic boundary conditions. The lower bounds of eigenvalues are presented.